Computation of wound rotor induction machines based on coupled finite elements and circuit equation under a first space harmonic approximation - Mezani, Smail; Hamiti, Tahar; Belguerras, Lamia; Lubin, Thierry; Gerada, Christopher (IEEE, 2015)
The paper presents a fast method to compute wound rotor induction machines in steady state. Coupled time-harmonic FE-circuit equation are used under a first space harmonic approximation for the air-gap magnetic field. It is shown that only 4 magnetostatic FE computations are necessary to determine the machine performances for any slip value. The performances comparison to a conventional complex magnetodynamic and time stepping FE analyses show the effectiveness of the proposed approach.